External shock financing and economic development: Implications for future reforms to the global financing architecture - Sherillyn Raga (Overseas Development Institute (ODI), 2024)
This report analyses the role that external shock financing can play in addressing the adverse impacts of external shocks in L&MICs. It summarises the growth impact of external shocks, maps out existing external shock financing facilities and instruments in the global financing architecture, and assesses the performance of external shock financing by the International Monetary Fund and the World Bank during the COVID-19 and Russia-Ukraine war crises.
Keywords: 330; Debt; Development banks; Development finance; Economic transformation; Economic growth; Financial systems; Resilience; Global; Russian Federation; Ukraine; COVID-19